Pengaruh Model Pembelajaran Scramble Terhadap Motivasi Belajar Siswa Kelas 2 SD Negeri 1 Kualasimpang - Warsinah Warsinah; Patri Janson Silaban; Lasma Silaban (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The learning motivation of grade 2 students at SD Negeri 1 Kualasimpang is still relatively low. This is shown by the lack of enthusiasm of students in participating in learning. This research aims to determine the effect of the Scramble learning model on the learning motivation of grade 2 students at SD Negeri 1 Kualasimpang. This research uses a quasi-experimental research design with a pre-test and post-test design approach. The research sample was 25 grade 2 students at SD Negeri 1 Kualasimpang. The research instrument used was a student learning motivation questionnaire sheet. The results of the research show that there is a significant influence between the Scramble learning model on the learning motivation of grade 2 students at SD Negeri 1 Kualasimpang. This is proven by the sig (2-tailed) value of 0.000 < 0.05. This research concludes that the Scramble learning model can increase the learning motivation of grade 2 elementary school students. The Scramble learning model can be an alternative learning model that can be applied by teachers to increase student learning motivation.